Comparison of microwave path lengths between temperate and tropical region based on effects of rain - Ulaganathen , Kesavan; Tharek , Abdul Rahman; Islam, Md. Rafiqul (2012)
Rain is a major source of attenuation for microwave propagation above 7 GHz. The problem of rain attenuation prediction has been studied along the years. In spite of the e®ort developed in di®erent parts of the world, there are yet some points to be clari¯ed. This problem is quite di±cult to be solved, mainly due to the complexity of rain structure. This clearly suggests that reduction factor is the major yardstick for comparing rain attenuation prediction models. However, important parameter need to consider in the path reduction factor is the maximum e®ective path length for a particular link at speci¯c operating frequency. This paper presents the summary of allowable path length for designing terrestrial microwave link at particular operating frequency at temperate and tropical region. The objective of this paper, to establish the maximum path length or hop length for terrestrial link on line of sight point to point communication at 99.99% of availability. Various frequency band such as 7 GHz, 15 GHz, 23 GHz, 26 GHz and 38 GHz been investigated using the ITU-R path reduction model. From the studies conducted, there are signi¯cant di®erences in path length between temperate region and tropical region. The di®erences are 22 km, 10 km, 5 km, 4km and 3km in the path length for operating frequency 7 GHz, 15 GHz, 23 GHz, 26 GHz & 38 GHz. This paper will provide useful information for microwave engineers and researchers in making valuable decision on path length for any terrestrial links point to point communication operating in a temperate and tropical region in future.